Професійно важливі характеристики психолога-консультанта : магістерський дослідницький проект - Гребенюк, Дарія Едуардівна (Одеса : НУ "ОЮА", 2024)
Психолог-консультант – це особа, що професійно, відповідально та на високому рівні надає психологічне консультування. Професійно важливі характеристики психолога-консультанта є ключовим аспектом його успішної практики та впливають на якість надання психологічної допомоги. Дослідження зосереджене на визначенні та аналізі низки факторів, що визначають високий професійний рівень консультанта. Важливим методологічним підґрунтям магістерської кваліфікаційної роботи є наукові праці вітчизняних і зарубіжних науковців, які професійно важливи якості психолога-консультанта. Ця робота базується на аналізі професійно важливих якостей практикуючих психологів-консультантів, використовуючи професіологічний підхід із включенням дослідження особистісних характеристик. У кваліфікаційній роботі надано результати вивчення професійно важливих характеристик психолога-консультанта. A counselling psychologist is a person who provides psychological counselling professionally, responsibly and at a high level. To do this, he or she must have a special higher psychological education and significant competence as a counsellor. This is necessary in order to effectively engage in counselling at a scientific level and provide competent answers to questions related to the client's mental state. According to Z.Y. Kryzhanovska, psychological counselling as a means of providing practical assistance in various situations of life is one of the most popular areas in practical psychology in modern conditions. However, the various definitions of the term "psychological counselling" indicate that there is no single set of concepts, terminology and theory in this field. An attempt to reconcile different approaches to this form of interaction with a person allows us to formulate the following description: psychological counselling is a direct interaction between a psychologist and a client (patient),is aimed at solving his/her personal problems, raising the level of psychological culture and personal development. B. Yakymchuk and I. Yakymchuk write in their manual that the role of a counsellor is to understand the essence of the counselling process. The main task of the counsellor is to help the client identify and overcome their internal difficulties. During counselling,9 clients should sincerely evaluate their behaviour and lifestyle and understand how and in what direction they want to change it. In his professional activity, a counselling psychologist should be understandable to the client and convincing to psychological specialists. Their task is to create a trusting environment where the client feels supported and able to disclose their problems, as well as to present counselling recommendations in accordance with the requirements of modern science and ethics of psychological practice. The concept of "professionally important qualities" encompasses a set of psychological characteristics of a person, as well as a number of physical, physiological and anthropometric parameters of a person that determine the success of learning and real life activities. A specific list of these qualities for each professional activity is formed on the basis of the results of psychological analysis of the activity and the creation of its occupational profile and psychogram. The goal of counselling is to help the client understand what is happening in his or her life and consciously achieve the goal, taking into account conscious choices in solving emotional and interpersonal problems. In addition, psychological counselling is a form of professional activity of a psychologist that implements the principles of psychological safety, hygiene and development. This includes rational, emotional, behavioural or systemic influences aimed at achieving psychological well-being, personal development, career progress and treatment of deviations. The relevance of the study is due to the need to reveal key aspects of professional activity in the field of counselling psychology. The growing demand for psychological help and counselling in modern society makes this research extremely relevant and necessary for the development of this field. Below are several arguments that emphasise the relevance of this study: - Growing demand for counselling services: In recent years, there has been a strong increase in the demand for counselling services due to the growing psychological difficulties among the population. Counselling psychologists are important figures in providing the necessary psychological support and assistance. The study of their professionally important characteristics is becoming a key element that determines the possibility of providing high-quality counselling services in response to the growing demand for such professional services. - Changes in modern working and living conditions: Risks of stress, adaptation to change, and interpersonal problems are increasing in the modern socio-cultural context. The study of the professional qualities of a counselling psychologist allows us to determine how effectively they can work in such changed conditions. - Improvement of professional training: Understanding the professional characteristics that define successful counselling practice is a key element in improving the training of future psychologists. The study can make a significant contribution to the development of psychological education and training. - Effectiveness of organisational counselling: In modern business and organisational management, consultancy services are gaining popularity. Studying the important characteristics of consultants will improve the quality of organisational consultations and contribute to the development of organisational psychology. Thus, the study is of great importance for the further development of psychology and counselling, providing a basis for improving the quality of counselling services and training a new generation of specialists.
Гребенюк Д. Е. Професійно важливі характеристики психолога-консультанта : магістерський дослідницький проект / Д. Е. Гребенюк. - Одеса : НУ "ОЮА", 2024. - 56 с.
Keywords: counselling psychologist; practicing psychologist; professionally important characteristics; психолог-консультант; практикуючий психолог; професійно важливі характеристики